New fossils of Mesopithecus from Hasnot, Pakistan. Issue 145 (August 2020) - Khan, Muhammad Akbar; Kelley, Jay; Flynn, Lawrence J.; Babar, Muhammad Adeeb; Jablonski, Nina G.
Abstract: Here, we report on a new collection of mostly isolated molars of a colobine monkey from near Hasnot on the Potwar Plateau of Pakistan. The specimens are from three late Miocene localities, with ages constrained to between 7.9 and 7.1 Ma. Morphological and metrical comparisons of the new Hasnot molars with those of previously recognized Mesopithecus species and living Asian colobines lead to the conclusion that the Hasnot colobine is most probably Mesopithecus, but not Mesopithecus pentelicus . The most morphologically distinctive aspect of the Hasnot specimens is the lower third molars, which exhibit large and bulbous protoconids set off by deeply incised mesial buccal and median buccal clefts and large, broad distobuccally placed hypoconulids. Colobine specimens previously recovered from the Potwar Plateau have been assigned to Mesopithecus sivalensis, but because these specimens have not yet been fully described, a detailed comparison with the new Hasnot specimens is not yet possible. For these reasons, we assign the new Hasnot colobine fossils to cf. Mesopithecus sp. Mesopithecus was one of the most widespread and successful of late Miocene primates. As a colobine equipped with features of the molar teeth, limbs, and, presumably, gut enabling it to succeed in more highly seasonal woodland environments, Mesopithecus was able to rapidly disperse into and adapt to the conditions in South Asia brought about by profound climatic and concomitant environmental change during the latest Miocene.